Changes in ecosystem services and an analysis of driving factors for China's Natural Forest Conservation Program. Issue 7 (9th March 2019) - Huang, Longsheng; Wang, Bing; Niu, Xiang; Gao, Peng; Song, Qingfeng
Abstract: China's Natural Forest Conservation Program (NFCP) is aimed at improving the fragile and unstable ecological environment and has become one of the largest ecological restoration programs in the world because of its enormous investment and effects. It is important to work out and strengthen new measures to overcome difficulties to promote more ecosystem services and human well‐being in the NFCP. This study focused on how to evaluate the ecosystem services change brought about by implementing the NFCP. Taking the key state‐owned forest areas in the Northeast and Inner Mongolia as the study area, we provide a basic overview of development and construct an evaluation index system and a distributed calculation method for the NFCP to analyze the implications of the NFCP on ecosystem services combined with multi‐source data coupling. An evaluation index system for NFCP ecosystem services was constructed. The system includes five ecological service functions and 12 evaluation indices. The trade‐off and/or synergistic analysis of ecosystem services were carried out. The regional characteristics and changes in the NFCP ecosystem services were emphasized. Although it has not been implemented for a long time, the NFCP has had a great impact on ecosystem services because it reduces soil and water losses, increases soil fertility, strengthens the forest carbon sink and helped the forest accumulate nutrients and purify the atmosphere. Socioeconomic factors affect the NFCP ecosystem services, such as the implementation area of NFCP, investment amount of NFCP, area ratio of nature reserves, and yield of tree stock volume. Policy drivers of the NFCP, changes in the economic structure and reductions in forest yield are the main factors affecting the change in NFCP ecosystem services. Although the NFCP has positively affected the society, the economy, and the ecological environment, it has also generated some problems, such as the improper management of forest resources, shortage of capital investment, staff transfer, etc. The social and economic problems will be transient with implementation of the NFCP, and the structural changes in forestry and agriculture may eventually benefit the forestry workers and other stakeholders. Abstract : In this work, taking the key state‐owned forest areas in the Northeast and Inner Mongolia as the study area, we provide a basic overview of development and construct an evaluation index system and a distributed calculation method for the China's Natural Forest Protection Program (NFCP) to analyze the implications of the NFCP on ecosystem services combined with multi‐source data coupling.